ANALISIS PERHITUNGAN BAGI HASIL DAN JASA TABUNGAN PADA BANK SYARIAH ( STUDI KASUS PADA BANK SULSELBAR CABANG SYARIAH MAKASSAR) - selfiana, selfiana; Wahyuni, Sri (Universitas Muhammadiyah Makassar, 2019)
This study aims to determine the calculation of profit sharing at Bank Sulselbar Makassar Syariah Branch. The types and sources of data used in the form of primary data: financial statements and mudharabah profit sharing and secondary data: company organizational structure, history and company activities. Data collection methods used in this study are Observation, Interview, Research Library, Documentation. While the data analysis used is descriptive quantitative. The results showed that the calculation of profit sharing and savings services at Sulselbar Bank Makassar Syariah Branch was in accordance with sharia principles as regulated in the DSN-MUI Fatwa based on the results of the mudharabah profit sharing analysis where the contract used was the mudharabah muthalaqah contract and the system used was revenue sharing system while the ratio used in mudharabah savings services is a quick ratio that banks are able to fulfill their obligations to depositors.